Brexit's effects on energy inflation in the UK - Kose, Nezir; Unal, Emre (Taylor & Francis Inc, 2025)
This study examined the effects of the Brexit referendum and the UK's official withdrawal from the EU on energy inflation by employing a difference-in-differences methodology to evaluate the implications of the policy change in the country. The study also takes into account the primary member states of the EU, namely France, Germany, and the Netherlands. This study demonstrated that the referendum held on 23 June 2016 and the subsequent official decision to leave the EU on 31 January 2020 did not have a significant effect on overall inflation. However, it did have a significant and positive impact on inflation rates in the energy and transport. Furthermore, the formal institutional shift had a more pronounced impact on energy inflation in comparison to the referendum. This highlights that the government's decision to exit the EU intensified the issue of inflation in the energy sector and its related transport domain inside the nation. This indicates that a nation departing from the EU may have inflationary issues, particularly in the sectors of energy and transportation. The findings indicate that implementing sustainable energy projects is a recommended approach to mitigate the substantial impact of Brexit on energy costs and the transportation sector in the UK.
Keywords: Brexit; difference-in-differences model; energy inflation; state-space model; transport inflation